Pelatihan Implementasi Kurikulum Merdeka di Sekolah bagi Guru Pendidikan Agama Islam di Kabupaten Garut: Meningkatkan Kualitas Pembelajaran PAI di Era Kurikulum Merdeka: Training on Implementation of Merdeka Curriculum in Schools for Islamic Religious Education Teachers in Garut Regency: Improving the Quality of Islamic Religious Education Learning in the Merdeka Curriculum Era - Fakhruddin, Agus; Anwar, Saepul; Romli, Usup; Firmansyah, Mokh. Iman; Faqihuddin, Achmad (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2025)
The Training on the Implementation of the Merdeka Curriculum for Islamic Education (PAI) Teachers in Garut Regency aims to enhance teachers' competencies in integrating the Merdeka Curriculum into Islamic Education teaching. This training covers six main topics: the philosophy of the Merdeka Curriculum, lesson planning, innovative teaching models, selection of teaching media, strengthening the Student Profile of Pancasila through projects, and authentic assessment. The training methods involve interactive face-to-face sessions, simulations, and self-learning using digital modules. The program's participants consist of 70 Islamic Education (PAI) teachers from primary schools in Bayongbong District, Garut Regency. Evaluation results indicate that participants highly appreciated the training, particularly in terms of material relevance and the expertise of the trainers. Most participants felt that this program helped them understand and implement the Merdeka Curriculum in their schools. This training significantly contributes to improving the quality of Islamic Education teaching and can serve as a model for similar professional development programs in other regions.